2016
DOI: 10.2215/cjn.05170516
|View full text |Cite
|
Sign up to set email alerts
|

Acute Kidney Injury in the Era of the AKI E-Alert

Abstract: The reported incidence of AKI is far greater than the previously reported incidence in studies reliant on clinical identification of adult AKI or hospital coding data. Although an electronic alert system is Information Technology driven and therefore, lacks intelligence and clinical context, these data can be used to identify deficiencies in care, guide the development of appropriate intervention strategies, and provide a baseline against which the effectiveness of these interventions may be measured.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
90
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(97 citation statements)
references
References 23 publications
7
90
0
Order By: Relevance
“…This could be due to limited follow-up time and insufficient power. On the other hand, patients who developed AKI of any etiology were shown to have a higher rate of ESRD (HR 2.57) when compared with those who did not and that is consistent with the known literature [19,20]. Upon comparing mortality and ESRD in patients that developed AKI (NCCT group), PC-AKI and no-AKI to each other (Fig.…”
Section: Discussionsupporting
confidence: 88%
“…This could be due to limited follow-up time and insufficient power. On the other hand, patients who developed AKI of any etiology were shown to have a higher rate of ESRD (HR 2.57) when compared with those who did not and that is consistent with the known literature [19,20]. Upon comparing mortality and ESRD in patients that developed AKI (NCCT group), PC-AKI and no-AKI to each other (Fig.…”
Section: Discussionsupporting
confidence: 88%
“…Short-and long-term mortality is increased in CA H -AKI [1,8] although HA-AKI is more likely to result in death [3,10,11] . Talabani et al [5] reported 45% 3-year mortality for CA H -AKI compared to 15.7% ( p < 0.01) in the control cohort with similar figures reported at 5 years (44.6% in Soto et al [7] ).…”
Section: Resultsmentioning
confidence: 99%
“…A similar percentage of non-repeat testing has been reported at 90 days (31%) for all AKI stages [12] . A recent national prospective cohort study demonstrated that CA P -AKI patients who were not hospitalized were more likely to result in CKD than those hospitalized [10] . Sawhney et al [12] reported low short-term mortality (2.6%) for AKI managed in primary care but substantial long-term mortality (46.2%) and a higher rate of progression to chronic RRT at 5 years compared to those admitted to hospital.…”
Section: C-aki Identified In Primary Carementioning
confidence: 99%
“…As a result most studies of AKI focus on hospitalised patients, and do not include all community acquired AKI, as a significant proportion of AKI in these settings do not result in hospitalisation . We have previously demonstrated that using the electronic AKI dataset provides a comprehensive characterisation of AKI across both community and hospital settings . Our data therefore provides a comprehensive overview of trends of all cases of AKI defined by changes in serum creatinine.…”
Section: Discussionmentioning
confidence: 99%
“…13 In addition to prompting clinicians to intervene at an early stage, this also provides a valuable source of data regarding the epidemiology of AKI. We have previously used this dataset to report the incidence and outcome of AKI in adult 14 and paediatric Dafydd Phillips and Oliver Young made an equal contribution to this manuscript patients 15 in Wales (UK). More recently we have demonstrated the significance of the electronic AKI alert in primary care.…”
Section: Introductionmentioning
confidence: 99%